Development of an automatic electrochemical flow system for high throughput determination of total antioxidant capacity in biological materials - Kornautchaya Veenuttranon; Loc Thai Nguyen; Anal, Anil Kumar; Sadiq, Muhammad Bilal; RTG Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
The aim of this work was to develop a programmable compressed - nitrogen gas flow system combined with electrochemical based assay for assessment of total antioxidant capacity (TAC) using the 2, 2 - diphenyl - 2 - picrylhydrayl hydrate (DPPH{u2022}) solution as a redox indicator on a screen printed carbon electrode ( SPE) . Gallic acid (GA) was chosen as a standard antioxidant. Firstly , the prototype device was designed and fabricated with an internal volume of 1,500 oL . A programmable electronic controlled 3 - way solenoid valve was utilized to control the liquid flow and retention time inside the reaction chamber of the system. A suitable driven pressure for compressed nitrogen gas was 20 kPa which was used to control the volumetric dosage of samples and reagents. There were a good linear relationship between propelled time and volumetric dosage (R 2 > 0.999 ) for all injection ports in which the linear regression equations were used to determine an accurate time for liquid injection . T he electrochemical characterizations of DPPH{u2022} and GA were performed using cyclic voltammetry (CV) , as a result, a suitable applied potential (E) of - 0.05 V was select ed for amperometric determination of TAC. The calibration curve was developed by measuring the constant currents of amperometry ( I ) for different concentration of GA in fixed 0.05 mM DPPH solution, after incubating the mixture for 2 min. One pure compound of ascorbic acid and four liquid food samples (orange juice, pomegranate juice, white wine and green tea) were mixed instead of GA and respective ( I ) were measured to determine the TAC. The results of TAC was then expressed in terms of gallic acid equivalent antioxidant capacity (GEAC). All the above experiments were co - conducted with the spectrophotometric analysis and results were compared. A good linear correlation (R 2 = 0.996 ) was obtained between electrochemical test within flow mixing system and conventional method of DPPH{u2022} scavenged by ascorbic acid, and two methods could be used interch ange (slope = 0.951 ). IC 50 and TAC of four samples were investigated by dif ferentiating the concentration and there was no significant difference (p> 0. 05) between the two methods.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Food Engineering and Bioprocess Technology, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2017
Keywords: Antioxidants -- Biotechnology; Biomaterials; Electrochemical apparatus